Integrative approach to graphic subjects teaching as a basis for forming design and technological competence - S. R. Gilyazova; T. A. Starshinova (Moscow Polytechnic University, 2022)
Positive sides of an integrative approach to teaching graphic disciplines are revealed in the article. Theoretical and practical aspects of forming design and technological competence areconsidered within the process of teaching integrative course "Descriptive geometry and engineering computer graphics".